AN ANALYSIS OF THE POLITENESS USED IN PODCAST “FRIENDS OF MERRY RIANA” - Melati (ReALL - Research on Applied Linguistics and Literature, 2023)
This study aims to identify and classify the politeness principles used and contained in Merry Rianna's podcast with Rudy Salim and Cinta Laura, and also to analyze the function of the politeness principles used and contained in Merry Rianna's podcast with Rudy Salim and Cinta Laura. The method used in this research is descriptive qualitative. The data collection technique used is the observation and note-taking technique. The object under study was a conversation on the podcast "Friends of Merry Riana" on the Merry Riana YouTube channel, October 17, 2022 edition and December 11, 2022. Based on the results of data analysis and the findings of this study, there were 20 politeness maxims, 11 objects of maxim agreement, 7 objects of maxim approbation, and 2 objects of maxim modesty and no violations of politeness maxims were found. The maxims that dominate the implementation of politeness maxims are the maxims of agreement maxim. The results of this study show that the use of language in the podcast show "Friends of Merry Riana" with guest stars Rudy Salim in the October 17, 2022 edition and Cinta Laura in the December 11, 2022 edition contains many utterances that are considered polite and do not go beyond their rights and deny their obligations.